PENGARUH KUALITAS PELAYANAN TERHADAP INDEKS KEPUASAN MASYARAKAT SESUAI STANDAR ISO 9001:2000 DI SAMSAT SURAKARTA - Damayanti, Niken - (JI@P, 2014)
This study works on seven variable independents predicted to have influencetoward customersâs satisfaction. Seven variables mentioned are time-liness (X1),service accusation (X2), courtesy and sociability (X3), patient responsibility inhandling customers (X4), rashness in getting service (X5), hospitality (X6) andtangible (X7). Objective of this study is to analyze the influence of qualityservice toward costumersâ satisfaction level according to ISO 9001:2000standards. Research was conducted in Surakarta Samsat. In the effort ofcomptence competitiveness, every Samsat office, especially in Central JavaProvince increases quality. Standard of quality is not only a criterion to wincompetition, but it is also as a qualification in some government offices and inthe private sectors as well. This study used survey method, however, interviewand documentation data collection techniques are employed as well. Data wascollected from 150 motor cycle taxpayers. Accidental sampling technique wasapplied. Multiple regression analysis technique were manipulated. Based onregression analysis statistical technique, data show that each of sevenindependent variables has significant influence toward customersâ satisfactionpartially as well as simultaneusly. Thus, hypothesis stating that seven variablespredicted to have influence toward customersâ satisfaction are supported.Keywords: time-liness, service accusation, courtesy and sociability, patientresponsibility in handling customers, rashness in getting service, hospitalityand tangible, customersâ satisfaction.